Perspectives on El Salvador - White, Ambassador Robert E. (Tufts Archival Research Center, 2005)
Volume 5, Issue 2. Summer The current situation in El Salvador is still in a state of violent turmoil. The Honorable Robert E. White, who has held many diplomatic posts including Deputy United States Representative to the Organization of American States, U.S. Ambassador to Paraguay, and, until the beginning of this year, U.S. Ambassador to El Salvador, agreed to talk to The Forum about El Salvador and current U.S. policy toward that country. This interview complements the Hars-Espinosa study which appears on pp. 295-319 of this issue. Ambassador White defines U.S. objectives in El Salvador and argues that any imposed solution to the present crisis which does not take cognizance of the political realities in El Salvador and which is not founded on the moral element of foreign policy which the American people demand, will only exacerbate the conflict. Mr. White graduated from The Fletcher School in 1954 and is presently Senior Associate at the Carnegie Endowment for International Peace.